PARTISIPASI PETANI DALAM PENERAPAN MINAPADI DI KABUPATEN SLEMAN - Winda Ika Permatasari; Suwarto Suwarto; Suminah Suminah (AGRITEXTS: Journal of Agricultural Extension, 2020)
This researchaims to examine the participation of farmers in the application of minapadi in Sleman Regency; examine the effect of non-formal education, experience, household income, paddy field area, group dynamics, and farming environment on farmer participation in the implementation of minapadi in Sleman Regency; and examine whether there are differences in farmer participation based on the farming environment in the application of minapadi in Sleman Regency. This research uses quantitative methods with survey techniques. The population in this study were farmers in the fish farmers group who received the Minapadi package program from the Agriculture, Food and Fisheries Service of Sleman Regency in Pakem District and Seyegan District. Samples using the Census method with 67 respondents as samples. Data analysis using multiple linear regression. The results of the study showed that the participation of farmers in the application of minapadi in Sleman Regency was in the moderate category. Participation factors simultaneously had a significant effect on farmer participation in the implementation of minapadi in Sleman Regency. Participation factors partially have a significant effect on farmer participation in the application of labor in the form of non-formal education, household income, and group dynamics while those that have no significant effect are experience, rice field area, and farming environment. There is no difference in farmer participation in implementing minapadi in Sleman Regency between upstream and downstream areas.